Proposed Hazard Analysis and Critical Control Point (HACCP) Plan for Production of Ready-to-Drink Fura-Da-Nono- A Review - Abdullahi, N.; Ndife, J.; Umar, N. B. (UMYU Journal of Microbiology Research)
The article intended to provide a concise and affluent proposal for the development of HACCP plan in the production of ready-to-drink Fura-da-Nono using information from reputable literature and guidelines recommend by food regulatory bodies. Poor personal hygiene, low quality raw materials and the rudimentary operations involved in the traditional processing of ready-to-drink Fura-da-Nono accounts for inconsistent quality, shorter shelf-life, poor hygiene and unacceptable qualities. During processing, materials are exposed to filthy processing environment, contaminated water, unclean processing equipment and contaminated packaging and storage containers. Application of HACCP guidelines in the production of ready-to-drink Fura-da-Nono will significantly improve its safety by assuring acceptance of only good quality raw materials and ensuring adequate processing along the production chain. These will not only guarantee the  safety of the finished product, but will also ensure better nutritional qualities and acceptable organoleptic properties.